Dexter Library staff, 1947 (1947)
Library staff. The 1947 El Rodeo Yearbook has a very similar photo that was taken at the same time. It lists, left to right: Pat Grube, Dorothy Wright, Ainsley Whitman, Evelyn Densmore, Beverly Bartron; second row: June Glenn, Walter Bonson. Ainsley Whitman was the head librarian from about 1946 - 1949.